Police officers giving evidence: Understanding the enablers and challenges of performance. (December 2019) - Brian, David; Cruickshank, Dr Andrew
This paper aimed to improve understanding of police officers performing as witnesses. Data was obtained by conducting semi-structured interviews and identified factors which enable and challenge an effective performance. Findings revealed specific appearance, behavioural, and cognitive enablers which underpin effective performance. Specifically, that performance is challenged by inconsistencies in police systems, poor training and preparation, anxiety, anticipation, and courtroom dynamics. These results indicate that police performance in court could be improved by producing appropriate systems to effectively manage anxiety and negative organisational narrative, as well as those that develop the appearance-, behaviour- and cognitive-based characteristics needed to achieve optimal performance.